Maternal Morbidity and Mortality in Higher Order Caesarean section - Shazia Iffet; Ayesha Arif; Sadaf Moin; Samia Ghulam; Nazia Mushtaq; Amera Tariq (ziauddin University, 2024)
Background: The persistently rising cesarean section rate in Pakistan is largely driven by cultural preferences for larger families, primary cesarean sections, induction of labor, and the desire to avoid litigation. These practices have resulted in numerous complications, posing significant challenges for obstetricians worldwide. This study aimed to determine the maternal morbidity and mortality associated with multiple repeat cesarean sections. Methods: This cross-sectional study was carried out at the Department of Gynecology and Obstetrics, at a tertiary care hospital, Abbottabad. Patients (106), with four or more previous cesarean sections, (elective or emergency repeat CS), over 6 months (October 2022 to March 2023), were selected. The primary outcome including uterine scar dehiscence (USD), scar rupture, bladder injury, bowel injury, grade 2 adhesions, morbidly adherent placenta (MAP), obstetrical hysterectomy, intensive care admission, blood transfusion, prolonged hospital admission, and maternal mortality, were recorded through follow-up four weeks postpartum. Data was analyzed using SPSS vr20. Results: Cesareans performed were 798, and HOCS 106 (13.2%). Out of these, 95 (89.6%) had their fourth, 9(8.5%) fifth, and 2(1.8%) sixth CS. Abdominopelvic adhesions were seen in 53(50%), USD in 23(21.6%), MAP in 5.6% leading to obstetrical hysterectomy in 6(5.6 %), bladder & bowel injury occur in 2(1.9%). No maternal death was recorded. Conclusion: HOCS pose significant challenges. Reducing primary and elective repeat CS rates by promoting alternative delivery methods and trial of labor after one CS. Proper counseling and education on the risks of multiple cesarean sections and the use of modern contraceptive techniques are essential.